THE IMPORTANCE OF METHODOLOGIES IN STUDYING PERSONALITY (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the importance of psychological methodologies in studying personality and their role in scientific research. The concept of personality, its psychological characteristics, and the main methodologies used in personality research are discussed. The article presents the content and practical significance of observation, interview, testing, questionnaires, and projective methodologies with examples. In addition, the scientific foundations of using psychological methodologies and the rules for their application are examined.
Keywords: Personality, psychology, psychodiagnostics, methodology, test, observation, interview, questionnaire, projective methods, personality traits.